2020
DOI: 10.2147/idr.s269971
|View full text |Cite
|
Sign up to set email alerts
|

<p>Carbapenemase Producers Among Extensive Drug-Resistant Gram-Negative Pathogens Recovered from Febrile Neutrophilic Patients in Egypt</p>

Abstract: Purpose This study aimed to detect the prevalence of carbapenemase producers (CPs) among extensive drug-resistant (XDR)-carbapenemase producing Gram-negative bacteria (GNB) recovered from various clinical specimens of hospitalized neutrophilic febrile patients in two major tertiary care hospitals in Egypt. Methods Standard methods were used to evaluate the antimicrobial susceptibility of clinical isolates according to the guidelines of the Clinical and Laboratory Standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 51 publications
7
10
1
Order By: Relevance
“…Both bla KPC and bla NDM genes were co-present in one isolate. The bla IMP gene was not carried in the plasmids of any of the tested isolates, which agreed with the results of other studies from Egypt reporting the absence of bla IMP gene from the tested CR-GNB isolates [ 48 , 52 ]. However, this does not negate the presence of IMP carbapenemase in Egypt, as it was reported to be harbored by P. aeruginosa isolates in Egypt in 2017 [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both bla KPC and bla NDM genes were co-present in one isolate. The bla IMP gene was not carried in the plasmids of any of the tested isolates, which agreed with the results of other studies from Egypt reporting the absence of bla IMP gene from the tested CR-GNB isolates [ 48 , 52 ]. However, this does not negate the presence of IMP carbapenemase in Egypt, as it was reported to be harbored by P. aeruginosa isolates in Egypt in 2017 [ 53 ].…”
Section: Discussionsupporting
confidence: 91%
“…Contrary to our results, a study on the epidemiology of CRE in Egyptian intensive care units reported that 117/236 (49.6%) Enterobacterales isolates from urine specimens were CRE, suggesting the presence of healthcare transmission [ 45 ]. Antimicrobial susceptibility testing showed that 64 out of 65 CR-GNB isolates were MDR, which was in accordance to previously published studies that underscore the considerable resistance of many CPs [ 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of its accuracy in detecting antimicrobial resistance genes, BFPP showed relatively high agreement when compared to VITEK-2 breakpoints, with PPA [100%, 93%, not applicable], NPA [97%, 85%, 90%], and OPA [98%, 90%, 90%] for carbapenemase producers, ESBLs, and MRSA, respectively. In comparison to other studies [28,[39][40][41] that reported on the prevalence of carbapenemase producers and ESBLs among HAP patients, our results revealed a higher rate of detection. This higher resistance rate could be attributed to the large use of antimicrobial agents among ICU patients, leading to more selective pressure and the appearance of different resistant phenotypes.…”
Section: Discussioncontrasting
confidence: 91%
“…A threatening rise in the incidence of carbapenem-resistant A. baumannii has been increasingly reported worldwide ( Levy-Blitchtein et al, 2018 ; Moghnieh et al, 2018 ; Alcantar-Curiel et al, 2019 ) and in Egypt as well ( Al-Hassan et al, 2019 ; Benmahmod et al, 2019 ; Mabrouk et al, 2020 ), leaving behind a substantial number of difficult to treat infections. For a deeper insight into the molecular mechanisms underlying carbapenem resistance in this highly problematic pathogen, a collection of 20 A. baumannii clinical isolates was screened for carbapenemase-coding genes by PCR.…”
Section: Discussionmentioning
confidence: 99%